THE IMPORTANT FACTORS OF TOURISM DEVELOPMENT IN SINGAPORE - Eko Suprayitno, Azhar Harun, (IQTISHODUNA, 2011)
This research paper will analyze the development of tourism industry in Singapore in which it focuses on the increasing number of tourist visit to Singapore, that contribute a significant source of tourism sector’s income and its role to generate the Singapore’s Gross Domestic Product (GDPS). The research aims to examine general characteristics of Singapore’s tourism industry and its role within the process of globalization. By applying the theoretical explanations, this research will observe several main questions: How the tourist locates Singapore as a tourist place and how they enter Singapore. In addition, what are the possible consequences on Singapore especially the influence on its National Income? The field research has been conducted at the most popular location of tourist area. Three equations had formed the hypothesis to answer those questions. First, the output of the study has shown that the price of consumer index (Index) have influence the increasing number of tourist to Singapore (TouS) in a positive way. Second, there are many other factors that contributed to the tourism sector’s income, however, the output of this study revealed only the total number of hotels in Singapore (HoS) is the major factors that contributed to the tourism sector’s income (ImS).